Improving mathematics interest and achievement through contextual teaching and learning - Siswanto, Deny Hadi; Andriyani; Rambe, Muhammad Yusuf (Journal of Professional Teacher Education, 2025)
This study is a Classroom Action Research (CAR) aimed at improving students' interest in learning mathematics through the implementation of the Contextual Teaching and Learning (CTL) model. The research subjects were 30 students from class XI Natural Science at Muhammadiyah Mlati High School (SMA Muhammadiyah Mlati) during the even semester of the 2023/2024 academic year. The study was conducted in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. Data collection was carried out through observations, interest in learning questionnaires, and learning outcome tests. The study's results showed a significant improvement in students' interest in learning. The average score for students' interest in learning increased from 1.76 (very low category) in the initial stage to 2.42 (low category) in cycle I, and reached 3.62 (very high category) in cycle II. In addition, students' learning outcomes also showed a remarkable improvement, with the average initial score rising from 34.4 to 56.1 in cycle I, and reaching 74.1 in cycle II, indicating that most students had met the Minimum Completeness Criteria. The results of this study imply that the application of the CTL model can be an effective strategy to increase students' interest and learning outcomes in mathematics, while also providing a basis for teachers, schools, and policy makers in developing more meaningful and contextual learning.